Multifocal calcifying fibrous tumor mimicking malignancy - Goyal, Binita (Journal of College of Medical Sciences-Nepal, 2016)
Calcifying fibrous tumor synonymous with calcifying fibrous pseudotumor is a rare benign mesenchymal tumor, recently been described in soft tissues. It is believed to be a true neoplasm with a tendency for nondestructive local recurrence. It presents as a single or multifocal well circumscribed but unencapsulated mass with variable size and may infiltrate into surrounding tissue. It is characterized histologically by hyalinized collagenous fibrous tissue, with bland spindle cells, psammomatous or dystrophic calcifications, and focal lymphoplasmacytic infiltrate. We present a rare case of multifocal calcifying fibrous tumors in retroperitoneum and in right adnexa in a 32-year-old female patient who presenting with pain in left lower abdomen. Imaging revealed large calcified solid mass lesion in right posterior para-renal space infiltrating into segment VI of liver and a similar smaller calcified mass in right adnexa which was confused with malignancy. JCMS Nepal. 2016;12(2):78-8.